젊은 남성에서 단안 눈꺼풀 부종을 동반한 일차 국소아밀로이드증 - 신혜은; 서유정; 정지원 (Daihan angwa haghoi jabji, 2023)
목적: 단안 상안검부종을 동반한 눈꺼풀결막에 발생한 일차 국소아밀로이드증 1예를 경험하였기에 이를 보고하고자 한다. 증례요약: 31세 남자 환자가 6개월 전부터 발생한 우측 상안검부종으로 내원하였다. 세극등검사 상에서 우측 눈꺼풀결막을 광범위하게 침범하는 출혈성의 유두 모양의 결막 병변이 관찰되었으며, 이는 거대유두결막염이 의심되는 소견이었다. 환자는 알레르기나 콘택트렌즈 사용 병력이 없었으며, 항염증제 점안에도 호전이 없어 절제생검을 시행하기로 하였다. 수술 중에 유두 모양의 병변은 수술칼에 의해 쉽게 벗겨지듯이 눈꺼풀결막으로부터 떨어져 나갔다. 병리조직검사에서 호산구성 비정형 물질의 침착이 관찰되었고 이는아밀로이드증에 해당하는 소견이었다. 전신아밀로이드증을 배제하기 위해 시행한 혈액검사, 흉부 및 복부 전산화단층촬영에서 특이소견은 없었다. 따라서 환자를 눈꺼풀결막에 발생한 일차 국소아밀로이드증으로 진단하였다. 1년 동안 경과 관찰하였으나 재발 소견은 보이지 않았다. 결론: 눈꺼풀결막에 발생하는 국소아밀로이드증은 드문 질환이지만, 본 증례와 같이 만성 눈꺼풀처짐 및 거대유두결막염과 같은 다양한 임상적 특징을 나타낼 수 있으므로 감별진단이 필요하다. Purpose: We report a young patient with unilateral eyelid swelling secondary to local, palpebral conjunctival amyloidosis. Case summary: A 31-year-old male was referred with a 6-month history of mild, right upper eyelid swelling but without redness or tenderness. Slit-lamp examination revealed a diffuse hemorrhagic papilliform lesion on the right upper palpebral conjunctiva, this raised a suspicion of giant papillary conjunctivitis. As the lesion was unilateral, there was no history of allergic disease or contact lens use, and the lesion was refractory to topical anti-inflammatory treatment so, excisional biopsy of the right upper palpebral conjunctiva was performed. During the operation, the papilliform lesion was removed, it peeled off on the blade. After surgery, the eyelid swelling improved. Histopathological examination revealed an eosinophilic amorphous deposit consistent with amyloidosis. Further evaluation ruled out systemic amyloidosis; there were no abnormal findings. Thus, we diagnosed primary localized amyloidosis of the palpebral conjunctiva. At the 1-year follow-up, no recurrence was detected. Conclusions: Although primary localized amyloidosis of the palpebral conjunctiva is rare, this should be considered if chronic eyelid swelling accompanied by another conjunctival lesion such as giant papillary conjunctivitis is encountered. KCI Citation Count: 0